A cross-lagged regression analysis of loneliness and depression: A two-year trace. Issue 2 (4th March 2022) - Ren, Lijie; Mo, Bibo; Liu, Junsheng; Li, Dan
ABSTRACT: This article aims to explore the possible causal relationship between loneliness and depression in college students. Two hundred and fifty-nine college students had been investigated four times in 2 years with UCLA and CES-D, and cross-lagged regression analysis was used. ① there was a significant positive correlation between loneliness and depression of college students; ② cross-lagged regression analysis showed that after controlling the related variables and the stability of variables themselves, loneliness, and depression could positively predict each other at points-in-time T1 and T2; Depression could significantly positively predict loneliness at points-in-time T2, T3, and T4. There is a bidirectional relationship between loneliness and depression of college students, and the effect of depression on loneliness is stronger than that of loneliness on depression.